2016
DOI: 10.3732/ajb.1500165
|View full text |Cite
|
Sign up to set email alerts
|

Effects of virus infection on pollen production and pollen performance: Implications for the spread of resistance alleles

Abstract: ZYMV infection adversely impacts the amount of pollen that can be donated to conspecifics, and pollen competition within the styles increases the probability that the ovules are fertilized by pollen from plants that are thriving when challenged by a viral disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 49 publications
0
10
0
1
Order By: Relevance
“…Overall plant growth was stunted by CMV infection ( S2 Fig ) but, interestingly, virus infection appeared to accelerate the appearance of flowers by a small but statistically significant degree ( S2 Fig ). A recent report indicated that flowers of squash ( Cucurbita pepo ) plants infected with the potyvirus zucchini yellow mosaic virus yielded decreased quantities of pollen [ 26 ]. However, we found no significant differences in the quantity or viability of pollen released from mock-inoculated and CMV-infected tomato flowers ( S3 Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…Overall plant growth was stunted by CMV infection ( S2 Fig ) but, interestingly, virus infection appeared to accelerate the appearance of flowers by a small but statistically significant degree ( S2 Fig ). A recent report indicated that flowers of squash ( Cucurbita pepo ) plants infected with the potyvirus zucchini yellow mosaic virus yielded decreased quantities of pollen [ 26 ]. However, we found no significant differences in the quantity or viability of pollen released from mock-inoculated and CMV-infected tomato flowers ( S3 Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…We have extensively studied the interactions among pathogens and herbivores in populations of Cucurbita pepo ssp. texana (e.g., Hayes et al, 2004 ; Stephenson et al, 2004 ; Ferrari et al, 2007 ; Du et al, 2008 ; Sasu et al, 2009 , 2010a , b ; Simmons et al, 2011 ; Shapiro et al, 2012 , 2014 ; Harth et al, 2016 ) under laboratory, greenhouse and field conditions. Cucurbita pepo ssp.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable evidence exists for wild radish (Marshall et al, 2010) and for other species (Rao et al, 1992; Havens et al, 1995; Demchik and Day, 1996; Agrawal et al, 1999; Lehtilä and Strauss, 1999; Galen, 2000; Pendleton, 2000; Galloway, 2001; Poulton et al, 2001a, b, 2002; Etterson and Galloway, 2002; Avila‐Sakar et al, 2003; Galen and Stanton, 2003; Hedhly et al, 2005) that environmental conditions for the pollen donor affect pollen and pollen tube quality. Generally, pollen donors grown under low water or low nutrients, exposed to herbivory, or affected by pathogens sire fewer seeds (Young and Stanton, 1990a; Lau and Stephenson, 1993; Quesada et al, 1995; Poulton et al, 2001b; Strauss et al, 2001; Pasonen et al, 2002; Hersch, 2006; Harth et al, 2016, in this issue). During our experiment, plants were used both as pollen donors and pollen recipients.…”
Section: Discussionmentioning
confidence: 99%